2005
DOI: 10.1111/j.0022-202x.2005.23702.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Anti-Type VII Collagen Antibodies Are Pathogenic and Responsible for the Clinical, Histological, and Immunological Features of Epidermolysis Bullosa Acquisita

Abstract: Epidermolysis bullosa acquisita (EBA) is an autoimmune blistering disease characterized by autoantibodies to type VII (anchoring fibril) collagen. Therefore, it is a prototypic autoimmune disease defined by a well-known autoantigen and autoantibody. In this study, we injected hairless immune competent mice with purified immunoglobulin G (IgG) fraction of serum from rabbits immunized with the non-collagenous amino-terminal domain (NC1) of human type VII collagen, the domain known to contain immunodominant epito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 37 publications
(40 reference statements)
2
85
0
3
Order By: Relevance
“…Because we injected mice with total anti-NC1 antibodies, we did not know in that study which epitope(s) was responsible for the disease induction. 21 Similarly, in the study reported by the Sitaru and colleagues, 22 they used a mixture of rabbit anti-mouse type VII collagen antibodies immunized from three peptides (residues 97 to 200, 479 to 587, and 757 to 967) within the NC1 domain to induce disease in the animals. Two of those peptides were generated using FINIII, the previously identified antigenic epitopes for EBA patient sera and another one consisting of half of the CMP subdomain (amino acid residues 97 to 200).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because we injected mice with total anti-NC1 antibodies, we did not know in that study which epitope(s) was responsible for the disease induction. 21 Similarly, in the study reported by the Sitaru and colleagues, 22 they used a mixture of rabbit anti-mouse type VII collagen antibodies immunized from three peptides (residues 97 to 200, 479 to 587, and 757 to 967) within the NC1 domain to induce disease in the animals. Two of those peptides were generated using FINIII, the previously identified antigenic epitopes for EBA patient sera and another one consisting of half of the CMP subdomain (amino acid residues 97 to 200).…”
Section: Discussionmentioning
confidence: 99%
“…We injected the antibody into hairless immunocompetent mice, and the mice developed a bullous eruption that had many of the features of EBA patients. 21 Another recent study by Sitaru and colleagues 22 showed that the injection of rabbit polyclonal antibodies to the NC1 domain of mouse type VII collagen into adult mice also induced subepidermal skin blisters reminiscent of human EBA. More recently, we affinity-purified anti-NC1 autoantibodies from EBA patients' sera and injected them into hairless mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Incubation of cryosections of normal human skin with sera of EBA patients followed by incubation with neutrophils from healthy volunteers leads to dermal-epidermal split formation [69]. Injection of antitype VII collagen antibodies in mice results in a skin disease that clinically and immunopathologically mimics the human disease [61, 67,[71][72][73]. While these models well reflect characteristic features of human EBA, they only reproduce the effector phase of EBA, i.e.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Moreover, the structure of the BMZ is altered in patients with epidermolysis bullosa acquisita, a disease characterized by the presence of autoantibodies that specifically target the NC1 domain, thereby altering formation of the NC1-stabilized structures [25,26].…”
Section: Introductionmentioning
confidence: 99%